Optimizing Human Resource Management Based on Techno-Entrepreneurship to Improve Employee Performance with Job Satisfaction at Adiwangsa University Jambi - Putri, Gaby Anissha; Toni, Nagian; Sutanto, Alex Tribuana; Marpaung, Fenny Krisna; Rosita, Rosita (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2026)
The rapid growth of the digital era demands higher education institutions to manage human resources effectively by integrating technoentrepreneurship values to enhance job satisfaction and employee performance. This study investigates the phenomenon at Universitas Adiwangsa Jambi, where differences in technology use, job satisfaction, and performance are still found. The research aims to analyze the influence of Human Resource Management and Technoentrepreneurship on Employee Performance with Job Satisfaction as an intervening variable. A quantitative survey was conducted on lecturers and staff, with samples selected using proportionate stratified random sampling based on the Slovin formula. Data were collected through a five-point Likert scale questionnaire and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS. Findings show that Human Resource Management and Technoentrepreneurship have positive and significant impacts on both Employee Performance and Job Satisfaction. Moreover, Job Satisfaction significantly improves Employee Performance and mediates the relationship between Human Resource Management, Technoentrepreneurship, and performance. Thus, effective HR management and technoentrepreneurship application enhance employee outcomes directly and indirectly.